The Reciprocal Interaction: Chemotherapy and Tumor Microenvironment - Kim, S.; Kuh, H.; Dass, Crispin (Bentham Science Publishers Ltd., 2011)
Despite significant improvements in ways to treat cancer, numerous patients still die from this disease. One of the reasons for this inability to cure cancer is the lack of ability of drugs to penetrate target cells properly. While studies on drug resistance have focused on the molecular mechanisms of single cells, there has been little attention on drug penetration or distribution in solid tumor tissues. It is reported that the factors that obstruct the penetration and distribution of drugs in solid tumors are closely related to the microenvironment of solid tumors. This review paper aims to discuss the microenvironment that hinders drug penetration in solid tumors and to investigate whether or not changes in the microenvironment can improve drug penetration. This review also introduces in vitro 3D multicellular culture systems that can reproduce the characteristics of solid tumors in vivo and that are required for such studies.